The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1149/1.3378967
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Binary Aliphatic Quaternary Ammonium Ionic Liquids: TMPAFSAxTFSA1-x

Abstract: The anionic binary Ionic liquids; TMPAFSA x TFSA 1-x were prepared as mixture of TMPATFSA and TMPAFSA. From the results of DSC analysis, the binary system showed the simple binary eutectic phase diagram and the eutectic point was found at the composition point of x = 0.33. In this system, each anion vibrated independently and showed isomerization equilibria displacement with temperature change. It was suggested that the equilibria displacements affected to the liquid structure and cistrans isomerization of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It was reported that TMPAFSA and TMPATFSA exhibit isomerization equilibria displacement depending on temperature, and alter its liquid structure depending on the isomerization equilibria displacement. 15 It was supposed that isomerization equilibria occurred during cooling processes until just before solidification and resulted in polymorphic behavior. We found difficulty to determine the crystal structure due to the polymorphism.…”
Section: Ionic Conductivity and Viscosity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that TMPAFSA and TMPATFSA exhibit isomerization equilibria displacement depending on temperature, and alter its liquid structure depending on the isomerization equilibria displacement. 15 It was supposed that isomerization equilibria occurred during cooling processes until just before solidification and resulted in polymorphic behavior. We found difficulty to determine the crystal structure due to the polymorphism.…”
Section: Ionic Conductivity and Viscosity Measurementsmentioning
confidence: 99%
“…In the past, authors found that mixture of TMPAFSA and N,N,N-trimethyl-Npropylammonium bis(trifluoromethanesulfonyl)amide (TMPATFSA) showed phase transition at lower temperature than each pure substance, and reported the phase diagram. 15 From the viewpoint of practical applications, mixing several materials is beneficial to design desired performances. 16,17 Although many studies have been investigated focusing on binary or ternary ionic liquid systems these are mainly limited in transport properties, and there are few studies about basic properties overlooking the whole composition.…”
Section: Introductionmentioning
confidence: 99%
“…To observing surface morphology of the PSi and carbon coated PSi, we used field emission scanning electron microscopy (FESEM; JEOL Ltd., JSM-6335F). amide ionic liquid was synthesized following the past report (13), and it was used for electrolyte. To infiltration the electrolyte, electrolyte loaded samples were set to under vacuum for overnight.…”
Section: Carbon Coated Psi Preparationmentioning
confidence: 99%